Development of Human Capital in the Labor Market in the Modernization of the Economy of Kazakhstan - Rysty Sabirova; Gulmira Andabayeva; Aiman Mussayeva; Zhanargul Bissembiyeva; Ainur Tazhidenova; Gulzhan Karimbayeva (Australasian Accounting, Business and Finance Journal, 2024)
Kazakhstan today is a country with a low level of economic development, although it has sufficient resources and manpower. The purpose of the study is to determine the specifics of human capital development in the labor market under the conditions of modernization of the economy of Kazakhstan. The analysis of economic indicators has shown that the financial stability of the country is at a low level. The study of the labor market has established that its labor supply is sufficient but low-promising. The perfect econometric modeling using the additive method of forecasting has shown that in the next two periods it should be expected an increase in the labor force. With the help of linear forecasting, it was established that in the next two periods of education and labor market reforms are not carried out, the economic situation of the country will continue to deteriorate.
Keywords: Cost of education; Enrollment in higher education; Labor force; Additive econometric forecasting model; Factor analysis.